Enteral Nutrition Feeding Adequacy among Mechanically Ventilated Critically Ill Patients with High Nutrition Risk in a selected Public Hospital in Malaysia : A preliminary study - Lee, Zheng Yii; Nisak, Mohd Yusof Barakatun; Airini, Ibrahim Noor (Bangladesh Critical Care Journal, 2016)
Background : Critically Ill patients with high nutrition risk require optimal amount of nutrition therapy for a better clinical outcome. Objective : The objective of this study was to study EN feeding adequacy among mechanically ventilated critically ill patient with high nutrition risk. Method : A prospective observational study was carried out at General Intensive Care Unit (ICU), Hospital Serdang. Adult patients (? 18 years old) who were intubated and mechanically ventilated within 48 hours of ICU admission, stayed in ICU for ? 72 hours and exclusively fed with EN were included. Eligible patients were followed in ICU for a maximum of 12 days or until death or discharge from ICU. High nutrition risk is determined by a validated nutrition risk screening tool -- the Modified Nutrition Risk in the Critically Ill (NUTRIC) score of ? 6. Results : A total of 25 patients were sampled. Mean age was 53 ± 17 years and mean BMI was 26.3 ± 5.3 kg/m2. Median time of EN initiation since ICU admission was 8 (Interquartile range [IQR] 3.5-17.5) hours. Among 17 (68%) patients with high nutrition risk, 15 (88.2%) did not receive the recommended optimal nutrition requirement (? 80% of calculated energy and protein requirement), despite the fact that the overall energy and protein adequacy was 71.8 ± 14.8% and 62.4 ± 15.1%, performing better than the international average of 61.2 ± 29.4% and 57.6% ± 29.6%, respectively. Conclusion : EN feeding adequacy was suboptimal among critically ill patients with high nutrition risk, as evidenced by 88.2% of high nutrition risk patients not receiving the recommended energy and protein requirement. Identification of patients with high nutrition risk is important to optimize nutrition intake in patients most likely to benefit from optimal amounts of nutrition therapy. Bangladesh Crit Care J March 2016; 4 (1): 9-13